Recent Increase in Methamphetamine Use in a Cohort of Rural People Who Use Drugs: Further Evidence for the Emergence of Twin Epidemics - Havens, Jennifer R.; Knudsen, Hannah K.; Strickland, Justin C.; Young, April M.; Babalonis, Shanna; Lofwall, Michelle R.; Walsh, Sharon L. (Frontiers in Psychiatry, 2022)
Appalachian Kentucky was at the epicenter of the prescription opioid epidemic in the early 2000s. As we enter the third decade of the epidemic, patterns have begun to emerge as people who use drugs (PWUD) transition from use of opioids to other drugs. The purpose of this analysis was to examine longitudinal changes in methamphetamine use in an ongoing cohort of rural people who use drugs (PWUD) in Appalachian Kentucky. All but five of the cohort participants (N=503) reported nonmedical prescription opioid use (NMPOU) at baseline and those 498 are included in this longitudinal analysis encompassing eight waves of data (2008-2020). Past 6-month use of methamphetamine was the dependent variable. Given the correlated nature of the data, mixed effects logistic regression was utilized to examine changes in methamphetamine use over time. Significant increases in methamphetamine use were observed over the past decade in this cohort of PWUD, especially in recent years (2017-2020). Prevalence of recent use at baseline and each of the follow-up visits was as follows: 9.4%, 5.6%, 5.0%, 5.4%, 8.1%, 6.8%, 6.9%, and 33.1%, respectively (p<0.001). On the contrary, significant reductions in NMPO and heroin use were observed in the same time period. The odds of methamphetamine use at the most recent visit were 25.8 times greater than at baseline (95% CI: 14.9, 44.6) and 52.6% of those reporting methamphetamine use reported injecting the drug. These results provide further evidence of “twin epidemics” of methamphetamine use among NMPOU. While problematic on several fronts, of particular concern is the lack of effective treatment options for methamphetamine use disorder. As policies around the opioid epidemic continue to evolve, particular attention should be paid to the surge in stimulant use in opioid-endemic areas.